PENGARUH GREEN PRODUCT DAN SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA PT. SENSATIA BOTANICALS - Ni Luh Bayu Okadiani; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2019)
Green product is a product that is not harmful to humans and the environment, not wasteful of resources, does not produce excessive waste and involves cruelty to animals, green products must consider environmental aspects in the product life cycle so as to minimize negative impacts on nature. Whereas social media marketing is one form of marketing using social media to market a product, service, brand or issue by utilizing audiences who participate in social media, so that later it will produce purchasing decisions. In this study using a non probability sampling method with a number of 100 respondents. The results of this study found that green products have a positive and signifcant effect on purchasing decisions at PT. Sensatia Botanicals with the regression value of the green product variable is 0.614.5), while social media marketing has no signicant effect on purchasing decisions at PT. Sensatia Botanicals.